Association of adolescents' knowledge, attitude, and practices on nutrition labels and their nutritional status - Nguyen, Marie Faye R.; Orillo, Anna Teresa O.; Hagos, Rose Ann F.; Javier, Celina Ann Z.; Alcantara, Richelle M.; Talavera, Maria Theresa M. (2011)
Nutrition labels play an important role in promoting proper nutrition. The purpose of the study was to establish the association of knowledge, attitude and practices (KAP) on nutrition labels in relation to the nutritional status of adolescents. Three hundred and ninety three (393) high schools students, aged 12 to 17 years old, were the respondents for the study.
Two sets of questionnaires were administered to determine the respondents (1) demographic characteristics; (2) dietary habits; and (3) knowledge attitudes, and practices (KAP) on nutrition labels.
Through descriptive statistics and Pearson correlation analyses, it was found that the respondents had high KAP rating on nutrition labels, positive attitude towards nutrition labels, and practice nutrition labels. Despite high KAP rating, the study found that KAP and nutritional status has weak (r=0.023, p=0.645) relations.
It can inferred that nutrition labeling alone is insufficient to improve the nutritional status of the group. Other contributing factors such as food habits, social influence, and accessibility to source of food habits, social influence, and accessibility to source of food with nutrition labels; information dissemination mechanism and presence of diseases are to be determined in order to further elucidate the association between nutritional labels and nutritional status.
Keywords: Nutritional status